A study on the level of awareness on the existence of small and medium industries loan scheme (SPIKS) among the SMI entrepreneurs in Kuching / Rokiah Ali - Ali, Rokiah (2005)
As SMI play a significant role in the industrial development of the state, government places an emphasis on the development of SMIs in Sarawak. In order to meet this objective, Sarawak Government has adapted some of the roles that are played by the Federal Government through their agencies such as SMIDEC where they are established to assist SMI entrepreneurs through their programs and financial package.